Overuse injuries in sport - Development, validation and application of a new surveillance method - Clarsen, B. (The Norwegian School of Sport Sciences, 2014)
Overuse injuries, defined as those without a specific, identifiable event responsible for their occurrence, may be a substantial problem in many sports. However, current surveillance methods in sports injury epidemiology studies, which rely heavily on time loss for injury definitions and severity measurement, may underestimate their true impact. This is because athletes often continue to participate in sport despite the existence of overuse injuries. The main aim of this dissertation was to develop a new method to record overuse injuries in sport, and to establish its validity by applying it in a number of different research settings Methods: This dissertation is based on three separate research projects. In the first project (Papers I and II) we developed the new method, including a new overuse injury questionnaire, and applied it in a 13-week prospective study of injuries among 313 athletes from five different sports: crosscountry skiing, floorball, handball, road cycling and volleyball. Standard injury registration methods were also used to record all time-loss injuries that occurred during the study period. In the second project (Paper III), the new method was applied in a 30-week study of risk factors for shoulder injuries among 206 elite male handball players. In the third project (Paper IV), we modified the new method so it could be used to monitor all types of health problems, including acute injuries, overuse injuries and illnesses. It was then used in a 40-week prospective cohort study of 142 candidates for the Norwegian team at the 2012 Olympic and Paralympic Games. Main Results: The new method captured over ten times as many overuse injuries as standard methods using a time-loss injury definition (Paper I). The area where overuse injuries had the greatest impact was the knee in volleyball where, on average, 36% of players had some form of complaint (95% CI: 32-39%) and 15% had substantial overuse problems (95% CI: 13-17%), defined as those leading to moderate or severe reductions in sports performance or participation, or time loss (Paper II). Shoulder injuries in handball were also prevalent. In paper III, the average prevalence of shoulder complaints was 28% (CI: 25% to 31%) and the average prevalence of substantial shoulder problems was 12% (CI: 11% to 13%). Significant associations were found between obvious scapular dyskinesis (OR 8.41, 95% CI: 1.47 to 48.1, p<0.05), total rotational motion (OR 0.77 per V 5° increase, 95% CI: 0.56 to 0.995, p<0.05) and external rotation strength (OR 0.71 per 10 Nm increase, 95% CI 0.44 to 0.99, p<0.05) and shoulder injury. In Paper IV, we found that an average of 36% of athletes had health problems during their preparation for the Olympic and Paralympic Games (95% CI: 34% to 38%), and 15% of athletes had substantial problems (95% CI: 14% to 16%). Overuse injuries represented 49% of the total burden of health problems, compared to illness (36%) and acute injuries (13%). Conclusions: The new method has good face, content and construct validity to record the full extent of overuse problems in sport, and we have demonstrated that it is feasible to apply the method successfully in studies of elite Norwegian athletes. We identified particular problem areas in a number of sports, such as the knee in volleyball and the shoulder in handball, for which continued injury prevention research focus is warranted. In the case of shoulder injuries in handball, injury prevention programs should address glenohumeral joint range of motion, external rotation weakness and scapular dyskinesis. The new method can be used to monitor not only overuse injuries, but also acute injuries and illnesses in heterogeneous groups of elite athletes.